Preparation, Process And Reading Of Results Of The Direct Preparation Ziehl Neelsen At Referral Public Health Centers In Surabaya - Dwi Lestari Pertiwi; Tjipto Rini (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
Tuberculosis Microscopic Reference of Public Health Center is a laboratory that is able to make preparations, staining and sputum microscopic examination, receive referrals and conduct technical guidance to branch of Public Health Centers, health workers in Public Health Centers playing the role of implementing health services are expected to ensure that the Main Tasks and Functions of health workers are in accordance with education and the skills they have. To ensure the accuracy of the results of microscopic sputum examination competence is needed. The competence referred to here is the ability to carry out or do a job that is based on skills and knowledge and is supported by the work attitude required by the job. This research was conducted in all Microscopic Referral of Public Health Centers in Surabaya in February 2013 - January 2014. The sample in this study was the health analysts of Microscopic Reference of Public Health Centers in Surabaya who had attended Tuberculosis microscopic training and were certified. The results of data analysis using the ANOVA test obtained Fcount value of 4.638 with a significance level of 0.030 that is less than 5% in preparation, a Fcount value of 11.573 with a significance level of 0.01 less than 5% in the process and a Fcount value of 4.603 with a significance level of 0.031 less than 5% on readings. This proves that there is a significant influence between the competence of health analysts on the preparation, process, and reading the results of direct preparations Ziehl-Neelsen.